On the Compatibility of the Diboson Excess with a gg-Initiated Composite Sector - Verónica Sanz (Advances in High Energy Physics)
We propose that recent results by ATLAS and CMS searching for heavy resonances decaying into bosons could be a first hint of a new sector of pure gauge confining physics, possibly linked to the origin of the Higgs as a Composite Higgs. The lightest resonances (glueballs) of this new sector would be neutral, spin-zero, and spin-two, and their behaviour would resemble that of a radion and a massive graviton of extra dimensions. We outline how 13 TeV LHC data could be used to improve sensitivity on this scenario, as well as future characterization during the 13 TeV LHC run.